Development of the “1+2+X” Modular Course System for Information Technology Majors from the Perspective of Dual-Mode IT - Ming Li; Hira Batool; Yun Mo; Guangyun Lu; Tuo Wang (Emerging Science Journal, 2023)
As the third generation of IT is developing rapidly, higher education institutions in China are looking to produce innovation-minded talent who can adapt to the dual-mode IT work environments of modern enterprises to meet the demands of the intelligent manufacturing national development strategy. So, this research aims to specify the hierarchical talent training system and mechanism for information technology majors in the higher education system. A 1+2+X modular curriculum system was proposed for the information technology majors based on the group-chain development model that focuses on combining discipline and industry (also known as vertical and horizontal integration). The data analysis was performed through a comparative analysis of the talent training objectives of the Chinese institutes and course systems’ national development strategies. The results support the idea that the 1+2+X modular curriculum system can help universities produce innovation-minded talent by designing their curriculum based on the industry and trends rather than just focusing on specialization training. The novelty of this research is that it promotes the idea of professional development along with course training. This paper recommends that future researchers implement the concept in vocational institutes. Doi: 10.28991/ESJ-2023-07-03-024 Full Text: PDF